When Did You Know You Were Straight? Teaching with the Heterosexual Questionnaire - Vooris, Jessica Ann (Radical Teacher, 2021)
This Teaching Note describes the process of forming a panel of straight students to answer questions from Martin Rochlin’s Heterosexual Questionnaire. The activity highlights heterosexism and heterosexual privilege, provides an opportunity to talk about satire and queer humor, and is a useful way to engage with concepts from class readings in introductory LGBTQ Studies and Women’s Studies courses.